Pelatihan Pembuatan Media Pembelajaran Aksara Jawa Bagi Guru Bahasa Jawa SMA di Kabupaten Rembang - Ermi Dyah Kurnia; Yusro Edy Nugroho (Jurnal Pengabdian Pada Masyarakat, 2017)
WORKSHOP OF PRODUCTION OF JAVANESE LETTER LEARNING MEDIA FOR JAVANESE TEACHER OF SENIOR HIGH SCHOOL IN REMBANG REGENCY. From the result of observation, it identified some Javanese Language teachers weakness in learning management of SMA/SMK/MA students in Rembang Regency, for example, the teachers still had a difficulty in developing learning media of Javanese letter. One of efforts to solve the problem was by giving the accompaniment in the form of training on how to produce Javanese letter learning media for the Javanese Language teachers of SMA in Rembang Regency. It is expected that the teachers have additional knowledge on Javanese letter learning media. The result of study showed that members of the activity had knowledge and skill of identification, production, and implementation of Javanese letter learning media. Based on the observation and evaluation of devotion team, it can be concluded that 1) the devotion activity was held according to the plan and can give the broader insight towards the members about Javanese letter learning media, 2) the devotion member enthusiasm in participating the activity was very high, 3) the activity members had the knowledge and skill in implementing Javanese letter media in learning process.